College and student activities at various colleges in Oxford University: Some lessons to Universiti Kebangsaan Malaysia. - Amy Poh Ai Ling,; Stephanie Kong Lee Keong,; Chan , Chee Lupp (Pusat Perkembangan Pelajar ,U.K.M, 2010)
This paper attempts to study on various colleges student activities, via a visiting survey deriving observation through informal interview and questionnaire collection in Oxford University, field research was conducted in St CrossCollege, Christ Churh College, Jesus College, Nuffield College, Somerville College and St Anthony College during the 15 days visit. With the increasing awareness on the goal of centre for student advancement, Universiti Kebangsaan Malaysia (UKM) to develop and produce wholesome graduates physically, spiritually emotionally and intellectually balanced and are able to master knowledge, we have design the research framework for the visit according to the objectives set by the university with the theme"Appreciating Similarities, Embracing Differences". from the survey, we analyze what is the best practice among the colleges. The analysis will mainly depend on the outcome of what the administrator, tutor and student perceive towards the college student activities.This paper discusses the college administration from diffent point of view, illustrates the needs of comparison for better from different perspective. A goal of this research was to introduce a more objective methodology focusing on the wellness of the residential college student activities management system as an alternative and more sustainable approach for benchmaking analysis. The main purpose of this program is to produce graduates who will accept lifelong learning and knowledge accumulation ,who are able to adapt to the exigencies oflife in various contexts through holistic learning, who are compititive as well as marketable both locally and in the internationally. The group consists of 3 bright student. This project is completely funded and sponsored by the centre for student advancement of UKM.